Produksi Varian Menu dan Kemasan Baru Produk Teh Di Pondok Modern Darussalam Gontor Darul Qiyam Magelang - Syaifullahil Maslul; Much. Iwan Agus Santoso; Achmad Rizal Syahruddin; Ahmad Alfan Arzaqi; Akhmad Novandi Nurtajuddin (PT.Mantaya Idea Batara, 2021)
Pondok Pesantren is one of the educational treasures in Indonesia. With a total education model, Islamic boarding schools have been able to survive to this day. Pondok Gontor is one of the Islamic Boarding Schools with many branches. One of branche is Pondok Gontor Darul Qiyam. Pondok Gontor Darul Qiyam has a tea factory business unit.The problem that occurred at the Tea Factory was the decline in competitiveness and buying interest from Darul Qiyam Islamic Boarding School students. On this basis, the students of the HES Study Program, Darussalam Gontor University, conducted the Thematic Community Service Program.The result of Thematic Community Service Programis the realization of three new variants of tea products from the Darul Qiyam Tea Factory, Jelly Milk Tea, Milk Tea Selasih and Lemon Tea Selasih. TThematic Community Service also initiated new packaging of tea products from Pondok Gontor Darul Qiyam Tea Factory.